Photodiode - Mallik, Arbind Kumar (Himalayan Physics, 2013)
Light detection is important for many types of electronic instruments. One of the most important of these light detecting tools is the photodiode. These tools are present in dozens of electronic devices. Photodiodes are semi-conductors that convert light into electrical voltage. This turns light signals into electrical input instructions that the machine can understand. Infect photodiodes are optoelectronic devices, meaning that they create electricity when light shines on them, similar to photovoltaic cells. In this article a brief about photodiodes are discussed. The Himalayan Physics Vol. 4, No. 4, 2013 Page: 95-98 Uploaded date: 12/23/2013